SURGICAL SAFETY IN CESAREAN SECTION: INTEGRATIVE REVIEW - Lara Mabelle Milfont Boeckmann; Maria Cristina Soares Rodrigues (Universidade Federal do Paraná, 2015)
Our goal was to gather and analyze scientific publications on surgical safety in cesarean deliveries through the following question: What is the scientific evidence for surgical safety in cesarean deliveries in the last 10 years? An integrative review of the literature was carried out in seven electronic databases between October and December 2014. We consulted the US National Library of Medicine, the Cumulative Index of Nursing and Allied Health Literature, Latin American and Caribbean Health Sciences Literature, the Medical Literature analysis and Retrieval System Online, the Cochrane Library, and the Nursing Database and Scientific Electronic Library Online. Four hundred and sixty-three articles were found, of which 11 were selected for analysis, and two central themes emerged: promotion of patient safety in cesarean deliveries by means of the surgical safety checklist and recommendations to improve quality of care in cesarean deliveries. Finally, few publications with high levels of evidence were found, which suggests the need for further studies to be carried out, particularly by nurses.